Interleukin 8 as predictive factor for response to chemotherapy in colorectal cancer patients. Issue 2 (4th March 2021) - Burz, Claudia; Bojan, Anca; Balacescu, Loredana; Pop, Vlad-Vasile; Silaghi, Ciprian; Lupan, Iulia; Aldea, Cornel; Sur, Daniel; Samasca, Gabriel; Cainap, Calin; Chiorean, Bogdan
ABSTRACT: Background : Colorectal cancer (CRC) represents a major public health problem owing to the fact that many patients are diagnosed in locally advanced or metastatic stage when chemotherapy is the only remaining option. However, treatment response is still unpredictable and depends upon a diversity of factors such as tumor inherited or acquired drug resistance and the host immune response to the malignant cells. The aim of this study was to evaluate the serum levels of interleukin 6, 8, 10 (IL-6, 8, 10) as possible predictive factors for response to chemotherapy and the correlation between the cytokines and the psychological distress. Methods : Forty-nine patients undergoing chemotherapy for locally advanced or metastatic CRC were included, for each patient IL-6, 8 and 10 were assessed through ELISA. Depression and anxiety were quantified through questionnaires. Statistical data were performed with GraphPad. Results : Patients with CRC had high serum levels of IL-8 and IL-6 compared to the healthy control group. High levels of IL-8 before treatment were correlated with progressive disease. There was a high incidence of psychological complication in CRC patients, especially in young male patients, from an urban area, with a positive correlation between serum levels of IL-8 and depression. Conclusions : These results indicate that high serum levels of IL-8 are predictive factors in CRC patients that undergo chemotherapy, but also could be useful in identifying psychological distress associated with this pathology.